2022
DOI: 10.1186/s12909-022-03683-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression symptoms and sleep quality with state-trait anxiety in medical university students in Anhui Province, China: a mediation analysis

Abstract: Background The prevalence of depression symptoms among medical students is particularly high, and it has increased during the COVID-19 epidemic. Sleep quality and state-trait anxiety are risk factors for depression, but no study has yet investigated the mediating role of state-trait anxiety in the relationship between poor sleep quality and depression symptoms in medical students. This study aims to investigate the relationship among depression symptoms, sleep quality and state-trait anxiety in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
(58 reference statements)
2
4
0
Order By: Relevance
“…With reference to the concurrent and predictive validity, the correlation results indicated that the sleep quality of sailors was related to depression and anxiety, which was in accord with the results of recent studies on the relationship between sleep disturbance and mental health among shift workers (J. Chen et al, 2022; Dai et al, 2019; Demirkol et al, 2021; Hwang et al, 2022; Yao et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…With reference to the concurrent and predictive validity, the correlation results indicated that the sleep quality of sailors was related to depression and anxiety, which was in accord with the results of recent studies on the relationship between sleep disturbance and mental health among shift workers (J. Chen et al, 2022; Dai et al, 2019; Demirkol et al, 2021; Hwang et al, 2022; Yao et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that the association was not significant. A potential reason is that the occurrence of anxiety/depression is complex and affected by many factors, including social participation (Ding et al., 2022), physical health (Almhdawi et al., 2021) and sleep quality (Chen et al., 2022). The non‐significant effect of family health on anxiety/depression may be related to the decomposition of other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that medical students are more likely to experience sleep deprivation than their peers in other fields, due to the intense academic and clinical demands of medical school [ 61 , 79 ]. This lack of sleep can profoundly impact medical students’ physical and mental health, leading to various negative effects [ 80 ]. The most obvious consequence of insufficient sleep is decreased alertness and focus [ 58 , 81 ].…”
Section: Discussionmentioning
confidence: 99%